Evaluating the book of technical writing (Arabs 101) in the technical colleges in the Kingdom of Saudi Arabia According of total quality standards - analytical study - Alqhtani, Raihanah Mosfer (Journal of Educational and Psychological Sciences, 2020)
The current research aims at highlighting to what extent the comprehensive quality standards of curriculum are found in the scope of objectives for ‘Technical Writing’ curriculum. The researcher has adopted a descriptive method for the study. As for the research tool, the researcher compares the quality of Technical Writing curriculum to comprehensive quality standards of syllabus. Technical Writing book (101), which is one of the subjects in technical colleges that belong to Technical and Vocational Training Corporation, was used as a sample for the research.‏The research has reached a number of results, the most important of which are: The overall quality standards were available in the general textbook of technical writing with a total of (385) repetitions, and a general average (38.4), and at the field level; first came the field: the language of the book with a total of 113 repetitions and an average of 11.3 out of 38.4 and 29.35% followed by artistic output with a total of 104 repetitions and an average of 10.3 out of 38.4 and 27%, followed by scientific content with 79 repetitions, an average of 7.9 out of 38.4 and 20.51%; all with a verbal assessment (large), and fourth came the field of assessment methods with a total of 65 repetitions and an average of 6.5 out of 38.4 and 16.88%, verbal evaluation (medium), and fifth came the field; the goals with a total of 19 repetitions and an average of 1.9 out of 38.4 and 4.93%, and finally the field of activities with a total of 5 repetitions, and an average of 0.5 out of 38.4 and 1.29%, both are verbal estimate (weak), It is recommended to reconsider the comprehensive quality standards for Technical Writing syllabus from General Administration for Curriculum in Technical and Vocational Training Corporation, particularly in areas of objectives and exercises.
Keywords: Assessment; Standards; Comprehensive quality; curriculum; syllabus